The Relationship between Family Health Task Implementationand the Incidence of Hypertension in Elderly - Ilham, Rosmin; Lasanuddin, Hamna Vonny; Bukulu, Deswita (Universitas Negeri Gorontalo, 2026)
The elderly experience various physical changes, one of which includes alterations in the cardiovascular system. A common disease that occurs in the cardiovascular system is hypertension. This study aimed to determine the relationship between the implementation of family health tasks and the incidence of hypertension in the elderly at the Kota Tengah Health Center in Gorontalo City. The research design utilized a correlational quantitative design with a cross-sectional technique. The population consisted of all elderly individuals at the Kota Tengah Health Center, totaling 90 people, with a purposive sampling technique used to obtain a sample size of 32 respondents. Data analysis was conducted using the chi-square test. The results indicated that the majority of the elderly had inadequate family health tasks, with 16 individuals (50%) experiencing hypertension, totaling 19 individuals (59.4%).in conclusion, there was a relationship between the implementation of family health tasks and the incidence of hypertension. It was recommended that families be educated on implementing their family health tasks, especially in managing elderly individuals with hypertension.